dear alex1981, pls. note that cos(pi/3) = 1/2 and not sqrt(3)/2 as you mentioned.

(sin (pi/3) = sqrt(3)/2).

Using the identity, cosec x =1/sin x , we get

2 sin^2 (pi/6) + (cos^2 (pi/3)) /(sin^2(7pi/6))

using the identity, sin (u+v) = sin u cos v +- cos u sin v

and writing 7pi/6 as (pi + pi/6), we get

2 sin^2(pi/6) + (cos^2(pi/3))/[sin pi cos (pi/6) +- sin (pi/6) cos pi]^2

using the values of sin and cos as sin (pi/6) = 1/2; cos (pi/3) = 1/2; sin pi = 0; cos pi = -1; we get

2 (1/2)^2 + [(1/2)^2]/[-+ 1/2]^2 = 2/4 + (1/4)/(1/4) = **3/2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now